Does patella alta lead to worse clinical outcome in patients who undergo isolated medial patellofemoral ligament reconstruction?: a systematic review - Bartsch, Anna; Lubberts, Bart; Mumme, Marcus; Egloff, Christian; Pagenstert, Geert (Archives of orthopaedic and trauma surgery, 2018)
The aim of this systematic review is to determine the effect of patella height on clinical outcomes after isolated MPFL reconstruction for patella instability. Our primary hypothesis is that patients with patella alta report similar outcomes after isolated MPFL reconstruction compared to patients with normal patella height.
Gesehen am 02.07.2020